Understanding Learner Interaction in Web Based Learning to Improve English Speaking Skills in Second Grade of SMAN 4 Senior High School Bandar Lampung: Using Canvas Learning Management System - Mendis, Upeka; Dharmawan, Yanuarius Yanu (Universitas Mathla'ul Anwar Banten, 2019)
Understanding learner interaction in web based learning to improve English speaking skills in second grade classroom of SMAN 4 senior high school Bandar Lampung: using canvas learning management system, English Study Program, Teacher Training Faculty of Bandar Lampung University.The objective of conducting this research is to find out the interaction in Canvas Learning management system (LMS) in the speaking classroom and effects of using Canvas LMS to improve speaking skills. After it is confirmed that there is indeed necessity behind the action, I will explain concepts of interaction, Canvas LMS and speaking skills. The participants of this research are students in second grade of SMAN 4 senior high school. They are selected as data resource to know about interaction and effects of using Canvas LMS. From them, I retrieve data to be analyzed. By giving questionnaire, observing and conducting independent sample t-test method gives me some findings to discuss. The results show that there is indeed necessity in doing English speaking lessons in Canvas LMS. Moreover it is about students’ interaction and effects to improve English speaking skills. First is about interaction, it is the main ingredient in any kinds of learning methods. There are three main types introduced my Moore (1989), there are learner-instructor, learner- learner and learner-content. Those types necessary appear in web based learning. These interactions lead to improve students’ speaking skills too.